School Size Effects Revisited A Qualitative and Quantitative Review of the Research Evidence in Primary and Secondary Education - Luyten, Hans.; Hendriks, Maria; Scheerens, Jaap.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book provides a thorough review of the research literature on the effect of school size in primary and secondary education on three types of outcomes: student achievement, non-cognitive outcomes and costs per student. Based on 84 scientific publications and several prior reviews, the book discusses four main areas: the impact of school size on cognitive learning outcomes and non-cognitive outcomes; the "state of the art" of empirical research on economies of size; the direct and indirect impact of school size, conditioned by other school context variables on student performance; and the specific position of the Netherlands in an international perspective. The book presents summaries of the results and main conclusions found and discusses these with respect to their relevance for educational policy in general and for the Netherlands in particular. The book concludes with suggestions for future research on school size.
1. Introduction; Jaap Scheerens, Maria Hendriks, Hans Luyten -- 2. School Size Effects: Review and Conceptual Analysis; Jaap Scheerens, Maria Hendriks, Hans Luyten -- 3. Research Synthesis of Studies Published between 1990 and 2012; Maria Hendriks -- 4. Quantitative Summary of Research Findings; Hans Luyten -- 5. Summary and Discussion; Hans Luyten -- Annex to Chapter 3.
Keywords: Education; International education; Comparative education; Educational policy; ducation and state; Assessment; Education; Educational Policy and Politics; Assessment, Testing and Evaluation; International and Comparative Education; Electronic books